Pengaruh Nilai Tukar dan Suku Bunga Bank Indonesia terhadap Deposito pada Bank Umum di Indonesia - Mochamad Taufiq; Sutopo Sutopo (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The aim of this research is to analyze the influence of the exchange rate and BI rate on deposits. The population in this study is all exchange rate data, BI rate and deposits from commercial banks in Indonesia. Sampling was taken by taking monthly data from the exchange rate, BI rate and deposits available from January 2014 to December 2023. The results of hypothesis testing show that hypothesis 1 (H1) that the exchange rate has a negative effect on deposits is proven and can be interpreted as meaning that an increase in the exchange rate will reduce amount of deposits at commercial banks in Indonesia. Hypothesis 2 (H2) that the BI rate has a positive effect on deposits is proven and can be interpreted to mean that an increase in the BI rate will increase the number of deposits at commercial banks in Indonesia.